Do homossexualismo à homoafetividade : discursos judiciais sobre as homossexualidades no STJ e STF de 1989 a 2012 - Thiago Coacci Rangel Pereira (2014)
This study investigates the main shifts produced in the judicial discourses present in the judgments of the Federal Supreme Court (STF) and the Superior Court Justice (STJ),specifically in the period between 1989 and 2012, to try to understand which have been the patterns of complexity the forms of state (here focused through the Brazilian Judiciary) exercise its power over the bodies and sexualities in recent decades and to identify whether there is a democratization of social and affective relations being operated by the Judiciary. The research was mainly documentary, analyzing qualitatively and quantitatively the STF’s and STJ’s judgments in which homosexuality was a central theme. The collection of judgments produced through a search performed by keywords in online repositories of case law of both courts. The research was configured to capture only judged judgments for the period January 1, 1989 until December 31, 2012. The words used for the search were: homossexual, homosexual, homossexuais, homosexuais, homossexualismo, homosexualismo, homossexualidade, homosexualidade, homoss$, homoafetivo, homoafetiva, homoaf$, homofobia, homof$, lesbofobia, gay, lésbica, bissexual, bisexual, bissexuais, bisexuais, sodomia. The words were chosen in order to try to capture the largest possible spectrum of cases. Data analysis identified a growth in the number of cases from the years 2008. It was possible to identify a strong trend of democratizing the social and emotional relationships through the Brazilian Courts, this trend became the majoritarian from 2011. However, the research also found a strong tendency to a familist assimilationism and the normalization of subjects, feelings and sexualities in heteronormative patterns.